NAVIGATING THE DIGITAL DIVIDE: ANALYSING THE IMPACT OF TECHNOLOGY AND CONNECTIVITY ON MODERN TRENDS IN INTERNATIONAL LABOR MIGRATION - Baxtiyor Zabixullayevich Fayzullayev; Dr. Summera Khalid (Journals Park Publishing, 2023)
In an era marked by globalization and the pervasive advance of digital technology, international labor migration has undergone a profound transformation. This research paper explores the dynamic interplay between technology, connectivity, and labor mobility in the 21st century. Drawing on insights from a rich body of literature, the study examines how the fusion of technology and globalization has reshaped labor migration processes. It investigates the digitalization of labor recruitment, the emergence of remote work and the gig economy, and the influence of social media on migration decisions. While technology has streamlined the flow of information, capital, and labor across borders, it has also exposed disparities in technology access, contributing to the digital divide. The rise of remote work and the gig economy has revolutionized labor migration, offering flexible work arrangements but also raising concerns about data privacy and worker rights. Social media has become an integral part of the migration journey, augmenting information flow and providing social support. Effective governance is crucial to balance technological advancements with the protection of worker rights and ethical labor practices in this evolving landscape. This research contributes to a nuanced understanding of the multifaceted impact of technology and connectivity on international labor migration, emphasizing the need for inclusivity, ethical considerations, and responsive policies. It recognizes that technology is a powerful force that can enhance opportunities but also demands vigilant attention to ensure the fair treatment and well-being of all individuals involved in global labor markets.
Keywords: International labor migration, Digital divide, Technology and migration, Remote work, Gig economy, Migrant workers' rights.